2001
DOI: 10.1034/j.1600-0587.2001.240201.x
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic feather mites synchronize dispersal and population growth with host sociality and migratory disposition

Abstract: Some symbiotic taxa may have evolved to track changes in the level and quality of food resources provided by the host to increase reproduction and dispersal. As a consequence, some ectosymbionts synchronize their reproduction and activity with particular stages of their host's living cycle. In this article we examined temporal patterns of variation in prevalence and abundance of feather mites living on pre‐migratory barn swallows Hirundo rustica. Feather mites in the lineages Pterolichoidea and Analgoidea are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 30 publications
1
52
1
1
Order By: Relevance
“…Some physical factors, such as temperature and rainfall, have been suggested to explain the seasonal differences in the intensity, abundance and prevalence of parasite species (Linardi et al 1985;Davidson et al 1994;Moyer et al 2002). Such associations may be related either with synchronization during the breeding period or dispersal of ectoparasites, as the stages of the life history of their hosts (Blanco and Frías 2001;Altizer et al 2004). Small mammals are often parasitized by larvae and nymphs of ticks, which are more active and abundant during the autumn and winter, which correspond to the dry season in the study area (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Some physical factors, such as temperature and rainfall, have been suggested to explain the seasonal differences in the intensity, abundance and prevalence of parasite species (Linardi et al 1985;Davidson et al 1994;Moyer et al 2002). Such associations may be related either with synchronization during the breeding period or dispersal of ectoparasites, as the stages of the life history of their hosts (Blanco and Frías 2001;Altizer et al 2004). Small mammals are often parasitized by larvae and nymphs of ticks, which are more active and abundant during the autumn and winter, which correspond to the dry season in the study area (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The main exception is the massive body of work by the Russian † Current address: Boyce Thompson Institute, Tower Road, Ithaca, NY 14853, USA Downloaded by [UQ Library] at 12:38 18 June 2015 76 Haribal et al 2011 feather mite biologist V. B. Dubinin, who published three massive volumes in the 1950s (1951,1953,1956) that documented the astonishing range of morphology, behavior and ecology displayed by these mites. Since Dubinin, a number of studies have looked at relationships between mite load and host condition (Blanco et al, 1997;Jovani and Blanco, 2000;Wiles et al, 2000;Blanco and Frias, 2001;, host behavior and mite numbers (Blanco and Frias, 2001) and molting status and mite distribution on feathers (Atyeo and Windingstad, 1979;Wiles et al, 2000). Seasonal phenologies of feather mites on hosts have been reported for a few species.…”
Section: Introductionmentioning
confidence: 98%
“…Various authors have suggested that mite abundances can be related to sex (Hamstra and Badyaev, 2008;Blanco and Frias, 2001;Blanco et al, 1999), mostly as a result of variations in hormone levels between different sexes (Blanco et al, 1999). Concurring with the findings from Galvan and Sanz (2006), Blanco et al (1997) and many others, the results of this study failed to find such associations for any of the species, indicating that the proposed variations in hormonal levels may not be strong enough to explain differences in mite abundances.…”
Section: Mite Abundance In Relation To Sex and Agementioning
confidence: 99%
“…Several studies found age to be important factor in determining mite abundances on birds, with mite loads usually increasing with increasing age (Hamstra and Badyaev, 2008;Blanco and Frias, 2001), attributed to the fact that mites are generally transferred from the female to the fledglings in the nest and then increase with reproduction and sociality over time (Galvan and Sanz, 2006;Figuerola, 2000;Poulin, 1991). As this study was carried out just prior to the breeding season, any effect of age may have been masked by the fact that juveniles have been exposed to infested adults throughout winter (high winter sociality) as suggested by McClure (1989).…”
Section: Mite Abundance In Relation To Sex and Agementioning
confidence: 99%